On the inverse problems for a family of integro-differential equations - Suhaib, Kamran; Ilyas, Asim; Malik, Salman A. (Mathematical Modelling and Analysis, 2023)
An integro-differential equation involving arbitrary kernel in time variable with a family of non-local boundary condition has been considered. Two inverse source problems for integro-differential equations are formulated and the unique-existence results for the solution of inverse source problems are presented. Some particular examples in support of our analysis are discussed.